IMPACT OF BONE MARROW-DERIVED MULTIPOTENT MESENCHYMAL STROMAL CELLS ON SPEED OF POLYCAPROLACTONE AND POLYHYDROXYALKANOATE SCAFFOLDS BIODEGRADATION - L. V. Antonova; A. Y. Burago; V. G. Matveyeva; Y. A. Kudryavtseva; M. V. Nasonova; Y. G. Toropova; E. A. Velikanova; A. S. Golovkin (Acta Biomedica Scientifica)
The impact of bone marrow-derived multipotent mesenchymal stromal cells of a bone brain (MSCs BB) on the speed of polycaprolactone and polyhydroxyalkanoate scaffolds biodegradation was studied. The presence of cells on the scaffolds surface was found to catalyze their resorption. 2 months after MSCs-covered scaffolds had. been subcutaneously implanted in rats they degraded completely while scaffolds, which had no MSCs cover, had partially resorbed by that time. The obtained results make necessary further studying of MSCs impact mechanisms on biopolymers resorption speed.